Persamaan Struktural: Aktivisme Institusi, Kepemilikan Institusional dan Manajerial, Kebijakan Dividen dan Utang - Mursalim Mursalim (Jurnal Akuntansi dan Auditing Indonesia, 2009)
This study investigated the simultaneity of five financial variables that are hypothesized to agency problem. It builds a model showing that institution activism, institutional and managerial ownership, dividend, and debt policy are determined simultaneously as each of the variables is hypothesized to decrease agency problem. Furthermore, the research is aimed at examining the effect of institution activism, ownership structure by institutional and managerial ownership on the financing decisions by dividend and debt policy. The research tested hypotheses by using Hausman’s specification test and two-stage least squares test. Hypotheses testing was conducted by using research sample of 70 manufacture company the registered in the Indonesia Stock Exchange during the years of 2000-2006. The samples determined by using a purposive sampling method. The research tested one hypothesis by Hausman’s specification test and the research result shows that institution activism, institutional and managerial ownership, dividend and debt policy are determined simultaneously to decrease agency problem.The research tested other hypotheses by two-stage least squares test. The research results shows that institutional ownership has a significant affects on the dividend and negative significant affects on the debt policy. Further results, that institution activism has a significant affects on the debt policy and institutional ownership, and that managerial ownership negative significant affects on the institution activism. Other result, that relationship a substitute between the institutional and managerial ownership. On the contrary, result shows that institution activism does not have a significant affects on the dividend policy, and the managerial ownership do not have a significant affects on the dividend and debt policy. Finally, this study shows that dividend policy do not have a significant affects on the debt policy.Keywords:    agency problem, institutional activism, institutional and managerial owner¬ship, dividend and debt policy.